Trimester-Specific Free Thyroid Hormones Levels among Pregnant Women in Nineveh Governorate,Iraq - Marrwa M.Naif; Hazim A.Allawi; Sura Khairialdeen Mohialdeen (College of Pharmacy University of Baghdad, 2024)
Abstract There are numerous physiological changes in thyroid gland functions occur during conception that lead to differ in thyroid hormones levels. Therefore, American Thyroid Association (ATA) guidelines recommended determination of population specific reference serum levels for thyroid hormones in different trimesters. Aim of current study is to establish trimester -specific reference serum levels (TSRSLs) for free triiodothyronine (FT3) and free thyroxine (FT4) in apparently healthy pregnant females in Nineveh governorate, Iraq. Accordingly, a cross-sectional study was carried out from Dec. 2020 to Apr. 2021 in Al-Batool Teaching hospital, Al-khanssa Maternity Teaching Hospital, Al-Noor Primary Health Center (PHC) and Out- patient clinics in Nineveh governorate. A total of 300 pregnant women were enrolled in this study after obtaining oral and written consent, 140 were excluded since they were met one or more of exclusion criteria, other 10 found to be positive anti-thyroid peroxide were also excluded from the study. The remaining 150 pregnant females aged (16-42) years were enrolled in this study, 50 of them were assigned to each trimester.The following parameters FT4 and FT3 were measured for each participants. The result of this study showed the TSRSLs of FT4 were (0.70-1.29, 0.49-1.31 and 0.58-1.28 ng/dl) for the 1st, 2nd and 3rd trim, respectively and for FT3 were ( 2.63-3.96, 2.04-3.3 and 2.11-3.40 pg/ml) for the 1st, 2nd and 3rd trim, respectively. The mean FT4 and FT3 was significantly decreased (P=0.002 and P<0.0001), respectively. from 1st to 3rd trim. The current study are reported the TSRSLs of FT3 and FT4 for the first time in Nineveh governorate. We concluded nearly similar TSRSLs of FT3 and FT4 to that recorded elsewhere